The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1542/peds.111.3.503
|View full text |Cite
|
Sign up to set email alerts
|

Internet-Enabled Interactive Multimedia Asthma Education Program: A Randomized Trial

Abstract: Supplementing conventional asthma care with interactive multimedia education can significantly improve asthma knowledge and reduce the burden of childhood asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
195
0
7

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 244 publications
(213 citation statements)
references
References 20 publications
9
195
0
7
Order By: Relevance
“…1). Of these 16 studies, 11 (69%) reported on randomised controlled trials (RCT) (10 two-arm RCTs [50][51][52][53][54][55][56][57][58][59], one three-arm RCT [60]) and 5 (31%) were feasibility studies employing a pre-post design [61][62][63][64][65] (Multimedia Apendix 2). Two of the RCTs reported on the same intervention [51,59], however, as they reported on different outcomes, and different uses of theory, we have considered them as separate interventions.…”
Section: Resultsmentioning
confidence: 99%
“…1). Of these 16 studies, 11 (69%) reported on randomised controlled trials (RCT) (10 two-arm RCTs [50][51][52][53][54][55][56][57][58][59], one three-arm RCT [60]) and 5 (31%) were feasibility studies employing a pre-post design [61][62][63][64][65] (Multimedia Apendix 2). Two of the RCTs reported on the same intervention [51,59], however, as they reported on different outcomes, and different uses of theory, we have considered them as separate interventions.…”
Section: Resultsmentioning
confidence: 99%
“…Doctors' offices and hospitals have taken an interest in supplementing asthma education given in a professional setting with technology based education methods [78,79]. Using a program based on the National Asthma Education and Prevention Program, one randomized control study consisting of children under age 18 years (n=246) tested the value of a new electronic educational tool called an "Interactive Multimedia Program for Asthma Control and Tracking" or IMPACT [79].…”
Section: Clinical Computer-based Educationmentioning
confidence: 99%
“…Using a program based on the National Asthma Education and Prevention Program, one randomized control study consisting of children under age 18 years (n=246) tested the value of a new electronic educational tool called an "Interactive Multimedia Program for Asthma Control and Tracking" or IMPACT [79]. The IMPACT program focused on asthma pathophysiology, triggers, medication, and self-management strategies and was met with notable success [79]. The intervention group showed an increase in asthma knowledge, reduced asthma morbidity, and reduced emergency room costs following program completion [79].…”
Section: Clinical Computer-based Educationmentioning
confidence: 99%
See 2 more Smart Citations